Backheel pass during forward running as a mechanism of severe acute hamstring injury in football: A case report - Markovic, G.; Karuc, I. (Clinical Journal of Sport Medicine, 2023)
Proximal hamstring tendon avulsions represent the most severe hamstring injury in sports and are typically sustained during stretch-related movements in closed kinetic chain: forced hip hyperflexion combined with knee extension. Here, we present the case study of the right-foot dominant professional football player with a severe proximal hamstring tendon avulsion injury and concomitant lower-grade injuries of hamstring muscle-tendon complex caused by a potentially new football-specific injury mechanism: right-foot backheel pass during forward running (ie, a kick directly backward). This mechanism involves a specific stretch-shortening cycle action of hamstring muscles in open-kinetic chain movement that has not yet been described in the scientific literature. Although further studies related to this football-specific hamstring injury mechanism are needed, clinicians and coaches working in football should be aware of it and potentially introduce additional injury mechanism-specific exercises and strategies for prevention of severe hamstring injuries which often require surgical intervention.